Building Functional Pervasive Computing Prototypes using Conductive Inkjet Printing - Kawahara, Yoshihiro; Hodges, Steve; Gong, Nan-Wei; Olberding, Simon; Steimle, Jürgen (IEEE Pervasive Computing Magazine, 2014)
Conductive inkjet printing with a consumer-grade inkjet printer can be used to create conductive circuits, including touch- and proximity-sensitive surfaces and other functional device prototypes. This easy, cheap, and quick process is relevant to a range of pervasive computing applications.